IDENTIFIKASI FUNGSI PARIT-PARIT KUNO DI PROVINSI LAMPUNG : The Identification of Moat Functions in Lampung Province - Rusyanti Rusyanti; Muhammad Suwongso Sadewo; Nanang Saptono (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2021)
Moat is one of the features that has been found in the past and has its local and contextual functions. Research by the Archaeological Center of West Java over the last two decades had found 35 moated sites associates with the findings from the 7th century to the 20th century. The function of these moated sites has long been questioned and left several options that have not been executed. As a desk study research, this paper aimed to reexamine the data classified within their geological settings and approached them with their ethnographical context to get closer to the precise functions of the moated sites. The result had found several functions of the moat based on their geological setting which is different from the highland and the lowlands, and their subsistence techniques within their moated land. Keywords: Lampung, moat, archaeology, subsistence